THE UNIFORM CPA EXAMINATION. - Hope, J. William (The Accounting Review, 1949)
Abstract A meeting of the American Accounting Association is a particularly good place for the Chairman of the Board of Examiners of the American Institute of Accountants to discuss the Uniform CPA Examination. It is here that the author would expect to find the sort of constructive criticism that can be most helpful in the continuing efforts of the board to supply an examination which will, if possible, better satisfy and more fairly serve the public, the profession, and the candidates, as well as the examining boards of forty-six states, four territories and the District of Columbia. There would be no law, and certainly not fifty-three of them requiring examination to prove the qualifications of those who would hold themselves out as capable of serving the public as certified public accountants, if the only purpose of such legislation was to serve the special interests of a favored few whose vanity had prompted them to secure for themselves a special designation placing them above their fellows.